2011
DOI: 10.2478/v10007-011-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of xanthan gum-facilitated ethyl cellulose microsponges for controlled percutaneous delivery of diclofenac sodium

Abstract: In this study, xanthan gum-facilitated ethyl cellulose microsponges were prepared by the double emulsification technique and subsequently dispersed in a carbopol gel base for controlled delivery of diclofenac sodium to the skin. Scanning electron microscopy revealed the porous, spherical nature of the microsponges. Increase in the drug/ polymer ratio (0.4:1, 0.6:1, 0.8:1, m/m) increased their yield (79.1-88.5 %), drug entrapment efficiency (50.0-64.1 %), and mean particle diameter (181-255 mm). Compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…The absence of crystallinity in the NaDic-NRL membrane indicates that NaDic is amorphous or molecularly disperse within the microparticles 25,26 . Amorphous NaDic has also been found by Li et al 27 , Manjunatha et al 28 , Lopes et al 29 and Maiti et al 30 showed barely irritant to rat skin.…”
Section: Resultsmentioning
confidence: 61%
“…The absence of crystallinity in the NaDic-NRL membrane indicates that NaDic is amorphous or molecularly disperse within the microparticles 25,26 . Amorphous NaDic has also been found by Li et al 27 , Manjunatha et al 28 , Lopes et al 29 and Maiti et al 30 showed barely irritant to rat skin.…”
Section: Resultsmentioning
confidence: 61%
“…Peaks at wavelengths corresponding to the pure drug were also observed in the microsphere formulation M4. The FTIR spectra of the pure drug and formulation indicated that the positions of characteristic peaks of CTZ were not altered after their successful entrapment in the microspheres, suggesting the absence of interactions between the drug and other components of the formulation (19).…”
Section: Ftir Studiesmentioning
confidence: 99%
“…22 Ethyl cellulose has been used successfully by several researchers for the development of topically applied microsponges and nanosponges, with enhanced performance. 17,[23][24][25] This present research aimed to develop lemongrassloaded ethyl cellulose nanosponges with topical hydrogel with an enhanced antifungal effect and decreased irritation, using the emulsion solvent evaporation technique. A 3 2 full factorial design was applied to investigate the effect of formulation factors on the in vitro release of lemongrass and the particle size of the prepared nanosponges.…”
Section: Introductionmentioning
confidence: 99%